Impact of Palm Oil Mill Effluent Towards Phytoplankton Community in Krueng Mane River, North Aceh - Muliari Muliari; Ilham Zulfahmi (Jurnal Perikanan dan Kelautan, 2016)
Palm oil mill effluent has potential as a pollutant and can reduce the aquatic productivity. One of the organisms potentially affected by palm oil mill effluent is phytoplankton.The study on the phytoplankton community in Krueng Mane river was done from July to September 2016. The objective of the present study was to evaluate the structure of the phytoplankton community in Krueng Mane river due to input palm oil mill effluent. The explorative survey was done at three sampling sites along the river. Sampling sites were determined based on purposive sampling method by looking human activity around the sites. The results show that there are seven classes of phytoplankton. The highest abundance of the phytoplankton was found at sampling site 2 (25.645 individual/liter). The diversity index showed that all of the sampling locations have a moderate degree of diversity, but the stations 2 have unstable community than the other two stations (E = 0.685).Saprobic coefficient indicates that station 2 included into moderate polluted β/α mesosaprobic